Healthcare workers’ beliefs, motivations and behaviours affecting adequate provision of sexual and reproductive healthcare services to adolescents in Cape Town, South Africa: a qualitative study - Kim Jonas; Rik Crutzen; Anja Krumeich; Nicolette Roman; Bart van den Borne; Priscilla Reddy (BMC Health Services Research, 2018)
Abstract Background Adolescents’ sexual and reproductive healthcare (SRH) needs have been prioritized globally, and they have the rights to access and utilize SRH services for their needs. However, adolescents under-utilize SRH services, especially in sub-Saharan Africa. Many factors play a role in the under-utilization of SRH services by adolescents, such as the attitude and behaviour of healthcare workers. The aim of this study therefore, was to explore and gain an in-depth understanding of healthcare workers’ beliefs, motivations and behaviours affecting adequate provision of these services to adolescents in South Africa. Methods Twenty-four healthcare workers in public SRH services in Cape Town, South Africa participated in this qualitative study through focus group discussions. To fulfill the aims of this study, nine focus group discussions were conducted among the SRH nurses. Results SRH nurses indicated that they are experiencing challenges with the concept and practice of termination of pregnancy. They explained that this practice contradicted their opposing beliefs and values. Some nurses felt that they had insufficient SRH skills, which hinder their provision of adequate SRH services to adolescents, while others described constraints within the health system such as not enough time to provide the necessary care. They also explained having limited access to schools where they can provide SRH education and pregnancy prevention services in the surrounding area. Conclusions Nurses are faced with numerous challenges when providing SRH services to adolescents. Providing the nurses with training programmes that emphasize value clarification may help them to separate their personal beliefs and norms from the workplace practice. This may help them to focus on the needs of the adolescent in a way that is beneficial to them. At the health systems level, issues such as clinic operating hours need to be structured such that the time pressure and constraints upon the nurse is relieved.